2015
DOI: 10.1038/ncomms8553
|View full text |Cite
|
Sign up to set email alerts
|

Inherited coding variants at the CDKN2A locus influence susceptibility to acute lymphoblastic leukaemia in children

Abstract: There is increasing evidence from genome-wide association studies for a strong inherited genetic basis of susceptibility to acute lymphoblastic leukaemia (ALL) in children, yet the effects of protein-coding variants on ALL risk have not been systematically evaluated. Here we show a missense variant in CDKN2A associated with the development of ALL at genome-wide significance (rs3731249, P=9.4 × 10−23, odds ratio=2.23). Functional studies indicate that this hypomorphic variant results in reduced tumour suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 39 publications
4
87
0
2
Order By: Relevance
“…Viral particles were prepared using the calcium chloride method in HEK293T cells and stable knockdown was established in the human lymphoid cell line Nalm6 (German Collection of Microorganisms and Cell Cultures, DSMZ) by lentiviral transduction of shRNA and puromycin selection, following procedures described previously 61 . Cell lines were authenticated by karyotyping and cytogenetics and tested negative for mycoplasma contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Viral particles were prepared using the calcium chloride method in HEK293T cells and stable knockdown was established in the human lymphoid cell line Nalm6 (German Collection of Microorganisms and Cell Cultures, DSMZ) by lentiviral transduction of shRNA and puromycin selection, following procedures described previously 61 . Cell lines were authenticated by karyotyping and cytogenetics and tested negative for mycoplasma contamination.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro differentiation assay of mouse HSPCs EP300-, CREBBP-, TCF3-, and TAF15-ZNF384 transcripts were cloned into the pcL20c-IRES-GFP lentiviral vector, and lentiviral supernatants were produced by transient transfection of HEK293T cells using calcium phosphate (Xu et al 2015). Lin…”
Section: Znf384 Target Gene Promoter and Enhancer Activity By Lucifermentioning
confidence: 99%
“…The NRAS G12D and CRLF2 constructs were gifts from Dr. Charles Mullighan at St. Jude Children's Research Hospital. Retroviral particles were produced using ecotropic HEK293T cells (American Type Culture Collection) (Xu et al 2015). Each experiment was performed three times.…”
Section: Sca1mentioning
confidence: 99%
“…Different underlying causes for the second, crucial step in the natural history of ALL (gene deletions or mutations that cause ALL) have been postulated, including aberrant reactions to infections in infancy and genetic variation in immune-response pathways (1). Germline variation can influence either step in this process, and case-control GWA studies have successfully identified ALL-associated SNPs in genes including ARID5B, IKZF1, CEBPE, PIP4K2A, CDKN2A/2B, and GATA3 (815). Supplementary Table S1 shows genes containing variants that have been associated with ALL in at least two GWA studies at a genome-wide significant level ( p < 5 x 10 −8 ).…”
Section: Introductionmentioning
confidence: 99%
“…To identify genes and gene subnetworks influencing genetic predisposition for ALL, we analyzed two datasets of p -values from previously published case-control ALL GWA studies (14,15) and p -values from an ALL case-parent trio study (25,26). We used the gene-level association method PEGASUS (20) to identify novel candidate genes associated with ALL.…”
Section: Introductionmentioning
confidence: 99%